Field reports form for submitting seasonal observations of Iowa birds, Tom Johnson, fall 1992 - Johnson, Thomas N.et al (1992)
Fall report of birds found at Rathbun Lake contributed by Tom Johnson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed